2023
DOI: 10.3390/electronics12102173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Augmented Reality (AR) on the Academic Performance of High School Students

Abstract: New technologies currently play a fundamental role in the educational context. As a result, augmented reality (AR) has recently gained a presence in educational centres. However, this educational technology has not been explored in depth at the secondary education level. Therefore, this research aims to analyse the impact of augmented reality on the academic performance of secondary education students, considering gender and the students’ attitudes toward this technology. In this mixed-method research based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…This finding aligns with some previous research indicating gender differences in technology adoption [21]. However, it contrasts with Amores-Valencia (2023), who reported no significant gender differences in attitudes towards AR, suggesting that such differences may vary by context or over time [22].…”
Section: Influence Of Demographic Variablessupporting
confidence: 89%
“…This finding aligns with some previous research indicating gender differences in technology adoption [21]. However, it contrasts with Amores-Valencia (2023), who reported no significant gender differences in attitudes towards AR, suggesting that such differences may vary by context or over time [22].…”
Section: Influence Of Demographic Variablessupporting
confidence: 89%
“…VR is a know-how that enables operators to entirely experience simulated surroundings using headsets or other gadgets as if they were actual (Lara-Acarez et al, 2023). VR has a strong and positive influence on educational outcomes (Amores-Valencia et al, 2023;Yu, 2021), with students assigning more consideration, having advanced feelings of attendance, and exhibiting more satisfaction (Huang et al, 2019), despite apprehensions on its clarity in the learning of mathematics (Cevikbas, Bulut and Kaiser, 2023), and negative effects on anxiety, cognition, creativeness, gender differences, learning attitudes, learner satisfaction, and engagement (Yu, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors and researchers have studied the theoretical and practical aspects of integrating AR technologies into the educational process. In particular, the study by Amores-Valencia et al (2023) aims to analyse the impact of augmented reality on the academic performance of secondary school students, taking into account gender characteristics and students' attitudes towards this technology. Using a mixed-methods study involving 321 students, they found that the use of augmented reality led to improved academic performance.…”
Section: Introductionmentioning
confidence: 99%